A reação das esquerdas brasileiras à ditadura militar: - Lemos, Marcos Antonio Amorim (Universidade Federal do Tocantins, 2023)
The present work discusses the reaction of the Brazilian leftists before the establishment of the military dictatorship, which lasted from 1964 to 1985. Our intention is to understand the strategies of action of different leftist groups that opposed the authoritarian measures imposed by the military government. To better understand this issue, we first made a bibliographical discussion mapping the main trends of the left, and later, we conducted an analysis of the Manual of the Urban Guerrilla, written by Carlos Marighella in 1969. Marighella was the leader of the ALN (National Liberation Action), Which advocated an armed reaction against the military dictatorship.